Role of f(R,T) Gravity in Bianchi Type-V Dark Energy Model with Electromagnetic Field based on Lyra Geometry - Brahma, B. P.; Dewri, M. (Journal of Scientific Research, 2022)
In this paper, a Bianchi type V Dark energy cosmological model scenario is studied with the electromagnetic field in Lyra based on f(R,T) gravity. The source of the magnetic field is along the x axis. Field equations found in Lyra geometry with electromagnetic field (F23 ≠ 0) in f(R,T) gravity, by choosing f(R ,T) = f1(R ) + f2(T) with f1(R ) + μR and f2(T) = μT. A hybrid scale factor discusses the physical and dynamical aspects of f(R,T) gravity.